A Bow‐Drill Structured Triboelectric Nanogenerator for Marine Ranching Monitoring. Issue 5 (7th December 2022) - Li, Jianping; Hu, Yili; Wang, Xiaoning; He, Lidong; Ma, Jijie; Wan, Nen; Wen, Jianming; Cheng, Tinghai
Abstract: Triboelectric nanogenerator (TENG) is one promising method of wave energy harvesting for marine ranching monitoring. Different from previous studies with complex structures (gears, racks, worm gears, or screw‐nut), a bow‐drill structured TENG (BS‐TENG) with a simple, cheap but effective rope‐roller structure is proposed and investigated to magnify the wave motion frequency. Inspired by the bow‐drill for carpentry, the proposed structure only simply needs a rope and roller to transfer the random wave motion into regular rotary motion with higher frequency. Results show that the structure parameters (flexible paddle number N P flexible paddle length L, electrode number N E and shaft side length D ) have a great influence on the working performance of the BS‐TENG. The maximum frequency magnification ration ( R m ) is 74 under the condition of 130 mm wave height ( H w ); the maximum output power ( P ) is 450 µW. Demonstration experiments verify that the BS‐TENG is able to charge the thermo‐hygrometer and light emitting diode lights for marine ranching. Combined with the Internet of Things and 5G technologies, the BS‐TENG could be applied in the offshore sensor system for the monitoring of marine ranching information. Abstract : A bow‐drill structured triboelectric nanogenerator (BS‐TENG) is proposed to magnify the wave motion frequency for wave energy harvesting. The maximum frequency magnification ration ( R m ) is 74 under the condition of 130 mm wave height ( H w ) and the maximum output power ( P ) is 450 µW. The BS‐TENG is applied in the offshore sensor for the monitoring of marine ranching information.